Defense Infrastructure Development Strategy in the Ibu Kota Nusantara Area - Aris Sarjito (Universitas Warmadewa, 2024)
This study explores the defense infrastructure development strategy in the Ibu Kota Nusantara (IKN) area, focusing on the current state, challenges, opportunities, and strategies for enhancement. The IKN area, strategically positioned amidst geopolitical tensions and technological advancements, presents a unique context for analyzing defense infrastructure. The research employs qualitative methods using secondary data, including policy documents, infrastructure reports, and scholarly articles. The findings reveal a well-distributed network of military installations and strategic assets in the IKN area, which enhances readiness but also exposes vulnerabilities such as geopolitical tensions and technological risks. Challenges include navigating complex geopolitical rivalries, integrating advanced technologies, and addressing environmental impacts. Opportunities exist in leveraging collaborative partnerships, adopting innovative technologies, and implementing sustainable practices. Strategies for enhancing resilience and effectiveness include adopting eco-friendly design principles, multi-layered defense planning, and capacity-building programs. The study concludes that a focused approach on resilience and adaptability is crucial for improving defense infrastructure and maintaining long-term security in the IKN area.